2020
DOI: 10.16899/jcm.767377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coronavirus (COVID-19) Pandemic on Health Anxiety Levels of Healthcare Professionals

Abstract: We aimed to determine the effects of the COVID-19 outbreak on health workers' health concerns and life. Methods: The study included 293 healthcare professionals reached via e-mail. A questionnaire created by researchers and health anxiety inventory were applied online to all participants. The questionnaire questions investigated the sociodemographic characteristics of the participant, whether he received psychological support during the COVID-19 outbreak, whether he had a chronic disease, whether he had proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
(16 reference statements)
0
10
0
3
Order By: Relevance
“…[7][8][9]18] Comparative studies, like our study, were limited. [6,20] In a study that was conducted with 59 doctors and nurses, some healthcare workers were found to show severe depressive symptoms. [21] In a broader study conducted with healthcare workers working in twenty different hospitals, the employees had depressed symptoms with a rate of 50.4%, anxiety symptoms with 44.6%, insomnia at 34%, and stress with a 71.5%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[7][8][9]18] Comparative studies, like our study, were limited. [6,20] In a study that was conducted with 59 doctors and nurses, some healthcare workers were found to show severe depressive symptoms. [21] In a broader study conducted with healthcare workers working in twenty different hospitals, the employees had depressed symptoms with a rate of 50.4%, anxiety symptoms with 44.6%, insomnia at 34%, and stress with a 71.5%.…”
Section: Discussionmentioning
confidence: 99%
“…After the stress and distress experienced, it is argued that the mental health of healthcare workers is at risk. [6] Many studies were conducted in the literature to evaluate the mental health of healthcare employees during the COVID-19 period. [6][7][8][9][10] In a study evaluating 134 healthcare workers, it was found that 12.7% of the participants showed depressive symptoms, and 20.1% showed anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The usual psychological reactions to pandemics can be at a healthy level or can reach the extent of disease. Anxiety, depression, fear, psychological stress, sleep problems are observed during the COVID-19 pandemic [3,4]. According to the study by Wang et al on the general population, it was found that the rate of moderate to severe depressive symptoms was 16.5%, the rate of moderate anxiety symptoms was 28.8%, and the rate of moderate stress was 8.1%.…”
Section: Introductionmentioning
confidence: 99%